Strategizing and the Initiation of Interorganizational Collaboration through Prospective Resourcing - Deken, Fleur; Berends, Hans; Gemser, Gerda; Lauche, Kristina (Academy of Management Journal, 2018)
In this paper, we explain how managers establish resource complementarity during their strategizing efforts for interorganizational collaboration. Based on a longitudinal field study at an automotive company, we show that resource complementarity is not given but jointly constructed in interactions with multiple potential partners through recursive cycles of what we refer to as “prospective resourcing.” Prospective resourcing mediates the interplay of strategizing and collaboration, thereby reversing the prevailing logic that strategy precedes and determines collaboration. Our findings offer insight into resourcing as a mechanism for developing strategic initiatives and shows how external actors may influence strategizing.